2016
DOI: 10.1007/s00192-016-3046-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of a posterior compartment procedure on symptoms of obstructed defecation and posterior vaginal compartment anatomy

Abstract: Introduction and hypothesis We hypothesized that there would be a significant difference in changes in obstructed defecation symptoms and posterior compartment prolapse between women who underwent posterior vaginal wall prolapse repair (PR) and those who did not. Methods This was a two-site prospective cohort study of women undergoing prolapse or incontinence surgery in which a PR was, or was not, performed at the discretion of the surgeon. Women were assessed using validated obstructed defecation questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the study, 40% of the patients had previous pelvic surgery and 59% of them reported at least some symptom of obstructed defecation. 4 In the present study, the mean age of the patients was 63.8 years. Fifteen patients (75%) had vaginal deliveries, with an average of 3 deliveries/patient.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In the study, 40% of the patients had previous pelvic surgery and 59% of them reported at least some symptom of obstructed defecation. 4 In the present study, the mean age of the patients was 63.8 years. Fifteen patients (75%) had vaginal deliveries, with an average of 3 deliveries/patient.…”
Section: Discussionmentioning
confidence: 57%
“…Disorders of the middle/posterior pelvic floor are complex, and it is difficult to correlate the symptoms (incomplete evacuation, fecal impaction, use of fingers to aid in the removal of stool and defecation effort) and the associated anatomical defects. Grimes et al 4 compared the surgical repair of the vaginal posterior wall prolapse associated or not with other pelvic procedures and concluded that this anatomical repair of the posterior compartment significantly improved all symptoms associated with evacuation difficulties, including fecal incontinence. In the study, 40% of the patients had previous pelvic surgery and 59% of them reported at least some symptom of obstructed defecation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surgical treatment aims at the anatomic reconstruction of the bowel and pelvic oor (14,15) and has been characterized by individual approaches. By ignoring the complexity of the underlying condition, the desired results are often missed (oder besseres Wort ?)…”
Section: Introductionmentioning
confidence: 99%